RITUAL ECONOMICS: ON THE EXAMPLE OF WEDDING RITUALS (ECONOMIC -ANTHROPOLOGICAL ANALYSIS) (Scientific journal of the Fergana State University, 2022)
This article analyzes the wedding ceremonies of the Uzbek and Kyrgyz residents of the Zааmin and Bakhmal districts of the Jizzakh region, one of the old districts of Ustrushena, considered part of Turonzamin, from an economic and anthropological point of view. It was also revealed that during the 20th century the ritual economy depended on the income of the family and the social environment of the community.